Fungus-feeding thrips of the genus Stephanothrips in Australia (Thysanoptera, Phlaeothripinae) - Mound, Laurence A.; Tree, Desley J. (Zootaxa, 2018)
Five species of Stephanothrips are now recorded from Australia, of which one is found worldwide, four are endemic, and two are described here as new species. S. broomei is remarkable for its colour pattern, and S. howei is only the fourth member of the genus to have a prominent hamus on the external margin of the fore tarsus. An illustrated key is provided to distinguish these five species.